2018
DOI: 10.1038/s41598-018-20724-3
|View full text |Cite
|
Sign up to set email alerts
|

Nemopilema nomurai jellyfish venom exerts an anti-metastatic effect by inhibiting Smad- and NF-κB-mediated epithelial–mesenchymal transition in HepG2 cells

Abstract: Epithelial–mesenchymal transition (EMT) is a key initial step in metastasis for malignant cancer cells to obtain invasive and motile properties. Inhibiting EMT has become a new strategy for cancer therapy. In our previous in vivo study, Nemopilema nomurai jellyfish venom (NnV) -treated HepG2 xenograft mice group showed that E-cadherin expression was strongly detected compared with non-treated groups. Therefore, this study aimed to determine whether NnV could inhibit the invasive and migratory abilities of HepG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 54 publications
2
16
0
Order By: Relevance
“…This target is a transcription factor and plays a decisive role in several biological processes, involving cell cycle regulation [ 42 ], cell differentiation, and apoptosis [ 43 , 44 ]. More importantly, it was strongly suggested that targeting NF-κB could be an effective direction for anticancer treatment, as it suppresses cancer cell migration and epithelia-mesenchymal transition [ 45 , 46 ]. Previous studies showed that targeting the NF-κB had anticancer effects in breast cancer [ 47 ], colon cancer [ 48 ], and esophageal cancer cells [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…This target is a transcription factor and plays a decisive role in several biological processes, involving cell cycle regulation [ 42 ], cell differentiation, and apoptosis [ 43 , 44 ]. More importantly, it was strongly suggested that targeting NF-κB could be an effective direction for anticancer treatment, as it suppresses cancer cell migration and epithelia-mesenchymal transition [ 45 , 46 ]. Previous studies showed that targeting the NF-κB had anticancer effects in breast cancer [ 47 ], colon cancer [ 48 ], and esophageal cancer cells [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The induction of EMT entails a reduction or loss of the ability to synthesize cytokeratins and E-cadherin by the epithelial and tumor cells, but the appearance of the ability to synthesize vimentin, Snail, smooth-muscle actin and other markers of EMT as well as an increasing expression of the genes encoding matrix metalloproteinases. As a result of EMT, cell–cell contacts are ruptured, cell morphology changes to fibroblast-like and the cells become mobile [27,29,30]. Additionally, in the process of EMT tumor cells acquire the properties of stem cancer cells, which are associated with high aggressiveness and drug resistance of malignant tumors [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Venom was extracted from the freeze-dried nematocysts using the technique described Lee et al 53 . In brief, venom was extracted from 50 mg of lyophilized nematocyst powder in 1 ml of cold phosphate buffered saline (PBS, pH 7.4, 4 °C) using glass beads.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting assay was performed as previously described 53 . Cells treated with NnV in the pretreatment and post-treatment of EGCG for 24 h were rinsed twice with ice-cold PBS.…”
Section: Methodsmentioning
confidence: 99%